Dynamic consequences of nonlinear radiative heat flux and heat generation/absorption effects in cross-diffusion flow of generalized micropolar nanofluid. (December 2021) - Ijaz Khan, M.; Al-Khaled, Kamel; Khan, Sami Ullah; Muhammad, Taseer; Waqas, Hassan; El-Refaey, Adel M.; Imran Khan, M.
Abstract: The double diffusion thermal mechanism of viscoelastic nano-materials has been suggested under the dynamic consequence of nonlinear thermal radiation and temperature absorption/production phenomenon. The electrically conducting generalized micropolar nanofluid is considered to predict the non-Newtonian behavior. The consideration of modified micropolar fluid successfully retained the viscous features as well as results for the second grade fluid. The uniform flow is induced with the linear movement of a flat surface. Following the convective boundary constraints, the heat and mass characteristics are reported. The equations that governs to the flow are reduced into ordinary ones. The homotopy analysis method (HAM) is imposed to develop the analytical expressions by using computational software MATHEMATICA 8 . The evaluation of parameters is inspected by performing graphical analysis for transport process. The computational numerically illustration of the local Nusselt number, Sherwood number and the motile microorganism density number is performed. The results claimed that nanofluid temperature declined with the vortex viscosity parameter. The solutal nanoparticles concentration decreases with the Dufour Lewis number while a lower change in solutal nanoparticles concentration has been observed for regular Lewis number. Moreover, the local Nusselt and Sherwood number increases with vortex viscosity parameter.